2012
DOI: 10.1097/scs.0b013e3182646043
|View full text |Cite
|
Sign up to set email alerts
|

Subconjunctival Injection of Triamcinolone for the Treatment of Upper Lid Retraction Associated With Thyroid Eye Disease

Abstract: Management of retraction of the upper lid during the congestive phase of thyroid eye disease is usually limited to conservative treatment. We evaluated the efficacy of subconjunctival injection of triamcinolone for the treatment of the upper lid retraction associated with thyroid eye disease.Thirty patients (43 eyes, 11 men and 19 women) with the upper lid retraction associated with thyroid eye disease were evaluated between May 2009 and September 2010. A dose of 0.5 mL of triamcinolone acetonide (40 mg/mL) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 18 publications
1
26
0
2
Order By: Relevance
“…Upper eyelid swelling was evaluated by the orbital fat around LPS muscle and the retro-orbicularis oculi fat (ROOF) thickness with sagittal MRI. To assess the potential for TA-induced complications, 22 24 intraocular pressure was measured before and at 1, 3, 6 and 12 months after treatment. Patients were also questioned about any other problems including menstrual disorders.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upper eyelid swelling was evaluated by the orbital fat around LPS muscle and the retro-orbicularis oculi fat (ROOF) thickness with sagittal MRI. To assess the potential for TA-induced complications, 22 24 intraocular pressure was measured before and at 1, 3, 6 and 12 months after treatment. Patients were also questioned about any other problems including menstrual disorders.…”
Section: Methodsmentioning
confidence: 99%
“… 21 24 Several reports suggested that subconjunctival TA injections resulted in an improvement of eyelid retraction in 68%–75% of patients from 1 to 4 times. 22 24 In addition, it was reported that such injection reduces inflammatory enlargement of the LPS muscle 23 and upper eyelid swelling. 24 However, subconjunctival TA injection causes increased intraocular pressure 22 24 and menstrual irregularities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al studied the effect of TA subconjunctival injection in patients in the active phase, and compared them with inactive, euthyroid patients 56. More profound improvement was found in the active group when compared with the inactive (86.3% of the patients in the active group showed improvement vs 25% of the inactive), as observed previously 54 55.…”
Section: Resultsmentioning
confidence: 70%
“…Local treatment with topical corticosteroids has been recommended as rst-line treatment for juvenile idiopathic arthritis (JIA)-associated uveitis, when the disease is mild and patients can be weaned relatively quickly off of steroid therapy [12,13]. The topical injection of hormone drugs such as triamcinolone acetonide or dexamethasone also has been used successfully for the treatment of thyroid-related ophthalmopathy [14,15]. Alkawas et al compared the e cacy of peribulbar triamcinolone acetonide to oral prednisone in the treatment of thyroidassociated ophthalmopathy.…”
Section: Introductionmentioning
confidence: 99%